Molecular composition of the intercalated disc in a spontaneous canine animal model of arrhythmogenic right ventricular dysplasia/cardiomyopathy - Oxford, Eva M. (2007)
BACKGROUND/OBJECTIVE: Arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is characterized by ventricular arrhythmias, sudden death, and fatty or fibrofatty replacement of right ventricular myocytes. Recent studies have noted an association between human ARVD/C and molecular remodeling of intercalated disc structures. However, progress has been constrained by limitations inherent to human studies. Here, we studied the molecular composition of the intercalated disc structure in a naturally occurring animal model of ARVD/C (boxer dogs). METHODS: We studied hearts from 12 boxers with confirmed ARVD/C and two controls. Ventricular sections from four animals were examined by immunofluorescent microscopy. Frozen tissue samples were used for western blot analysis. Proteins investigated were N-cadherin, plakophilin 2, desmoplakin, plakoglobin, desmin, and connexin43 (Cx43). RESULTS: In control dogs, all proteins tested by immunofluorescence analysis yielded intense localized signals at sites of end-to-end cell apposition. In contrast, myocardial tissues from ARVD/C-afflicted boxers displayed preservation of N-Cadherin staining but loss of detectable signal for Cx43 at the intercalated disc location. Western blots indicated that the Cx43 protein was still present in the samples. Gene sequencing analysis revealed no mutations in desmoplakin, plakoglobin, Cx43, or plakophilin 2. CONCLUSIONS: Mutation(s) responsible for ARVD/C in boxers lead, directly or indirectly, to severe modifications of mechanical and electrical cell-cell interactions. Furthermore, significant reduction in gap junction formation may promote a substrate for malignant ventricular arrhythmias. This model may help advance our understanding of the molecular basis, pathophysiology and potential therapeutic approach to patients with ARVD/C.